Mechanical Properties of Natural Rubber Reinforced with Modified Silica by Admicellar Polymerization - ประจักษ์สูตร์, ธัมม์โชโต; ปิติฤกษ์, คมกฤช; พงศ์ประยูร, ถิราวุธ (Research on Modern science and Utilizing Technological Innovation Journal (RMUTI Journal), 2019)
Carbon Black (CB), Unmodified Silica (Si) and silica modified by admicellar polymerization (MS) were applied as rubber reinforcement. Mechanical properties of these different rubber formulae were subsequently tested. The results revealed that the mechanical properties of rubber reinforced with silica modified by admicellar polymerization were superior to those reinforced with carbon black or unmodified silica. As for the rubber reinforcement with silica modified by admicellar polymerization at the 40 phr (Parts Per Hundred of Rubber) mixture ratio with a compression mold at 160 kg/cm2 at a 145 °C cure temperature for 4 minutes proved to be the best mechanical properties effective and the most optimal conditions to be used as a rubber chemical formulae for production of inner rubber tube products.